2005
DOI: 10.1126/science.1120640
|View full text |Cite
|
Sign up to set email alerts
|

Equivalent Effects of Snake PLA2 Neurotoxins and Lysophospholipid-Fatty Acid Mixtures

Abstract: Snake presynaptic phospholipase A2 neurotoxins (SPANs) paralyze the neuromuscular junction (NMJ). Upon intoxication, the NMJ enlarges and has a reduced content of synaptic vesicles, and primary neuronal cultures show synaptic swelling with surface exposure of the lumenal domain of the synaptic vesicle protein synaptotagmin I. Concomitantly, these neurotoxins induce exocytosis of neurotransmitters. We found that an equimolar mixture of lysophospholipids and fatty acids closely mimics all of the biological effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
170
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 183 publications
(176 citation statements)
references
References 19 publications
6
170
0
Order By: Relevance
“…These data support the idea that PA might promote fusion via a biophysical mechanism. In this regard, it should be noted that a recent study by Rigoni et al (36) found that the biological effects of snake phospholipase A2 neurotoxins, which induce massive exocytosis of neurotransmitters and depletion of synaptic vesicles, can be mimicked by the incubation of nerve terminals with an equimolar mixture of lysophospholipids and fatty acids. They concluded that local lipid changes such as the accumulation of positive curvaturepromoting lipids (such as LPC) in the outer leaflet of the plasma membrane or negative curvature-promoting lipids (such as PA) in the inner leaflet of the plasma membrane might be of functional significance in synaptic vesicle release.…”
Section: Discussionmentioning
confidence: 99%
“…These data support the idea that PA might promote fusion via a biophysical mechanism. In this regard, it should be noted that a recent study by Rigoni et al (36) found that the biological effects of snake phospholipase A2 neurotoxins, which induce massive exocytosis of neurotransmitters and depletion of synaptic vesicles, can be mimicked by the incubation of nerve terminals with an equimolar mixture of lysophospholipids and fatty acids. They concluded that local lipid changes such as the accumulation of positive curvaturepromoting lipids (such as LPC) in the outer leaflet of the plasma membrane or negative curvature-promoting lipids (such as PA) in the inner leaflet of the plasma membrane might be of functional significance in synaptic vesicle release.…”
Section: Discussionmentioning
confidence: 99%
“…Principally, different pathways can generate PA: (1) hydrolysis of phospholipids via PLD (Bader and Vitale, 2009), (2) phosphorylation of diacylglycerol (DAG) by DAG kinase (Yang et al, 2011), and (3) acylation of lysophospholipids by lysophospholipid acyltransferases ). Lysophospholipids, substrates of the latter reaction, are generated under various physiological and pathophysiological situations at various cell organelles, e.g., the endoplasmic reticulum, Golgi apparatus, endosomes, and presynaptic terminals (de Figueiredo et al, 2001;Chambers et al, 2003;Ong et al, 2005;Rigoni et al, 2005;Rossetto and Montecucco, 2008;Schmidt and Brown, 2009;Oliveira et al, 2010;Vitale et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…CGN neurons are highly sensitive to SPANs and develop a well-defined bulging at axon and dendrite terminals within few minutes from toxin addition; such morphological alteration is accompanied by cytosolic calcium increase at nerve terminals and glutamate release from neurons (Rigoni et al 2004(Rigoni et al , 2007. These effects are mimicked by the addition of an equimolar mixture of the PLA 2 hydrolysis products, lysophosphatidylcholine (LysoPC) + oleic acid, indicating that these molecules are the biochemical mediators of SPAN action (Rigoni et al 2005;Caccin et al 2006). Of the two lipid molecules, LysoPC was shown to be most effective (Caccin et al 2006(Caccin et al , 2009.…”
mentioning
confidence: 93%